Cost-Effectiveness of Life Cycle Cost Theory-Based Large Medical Equipment - Xiaoyi Chang; Yongqiang Zhao; Yuebin Li; Ting Bai; Jungang Gao; Chao Zhao (Applied Bionics and Biomechanics)
The purpose of this study is to use the life cycle cost theory to analyze the efficiency of large medical equipment in hospitals, so as to implement life cycle cost (LCC) management and solve the current problems in hospitals. The analysis model of cost benefit of large medical equipment is established, and the cost-effectiveness of 4 large medical equipment between 2019 and 2021 is investigated and analyzed. In terms of the data in each information system of hospitals, the utilization of large medical equipment is quantitatively evaluated and analyzed by life cycle theory. The results show that the Revolution 256 row has the highest revenue of 113.29%. The annual depreciation of Signa 3.0 T HDxt is the highest, amounting to 4,160,000 yuan. However, there is lack of quality control and preventive maintenance of most equipment during use. The cost and benefit of large medical equipment in hospitals are analyzed, which demonstrates that Signa 3.0 T HDxt shows better effectiveness. Too high hospital warranty cost reflects the weak maintenance strength of hospital engineering technicians. The fundamental point of the maintenance and management of large medical equipment is to strengthen the performance evaluation of medical engineering technicians.